(untitled) (Journal of Medicine, 2008)
To check negligence or malpractice in health-care service, or to check the deviation from the general accepted standard of the health-care service providers in Bangladesh proper legal protection against it is the demand of the time. The remedy against such medical malpractice has well been developed in United States (US) Law system. However, we are lagging far behind. This article has made an attempt to define "medical malpractice" and has rendered a bird’s eye view on United States (US) law as a model study and has talked about it in Bangladesh perspective. Â DOI = 10.3329/jom.v9i2.1437 J MEDICINE 2008; 9 : 87-89